Comparative efficacy and tolerability of 32 oral and long-acting injectable antipsychotics for the maintenance treatment of adults with schizophrenia: a systematic review and network meta-analysis - Schneider-Thoma, Johannes; Chalkou, Konstantina; Dörries, Carola; Bighelli, Irene; Ceraso, Anna; Huhn, Maximilian; Siafis, Spyridon; Davis, John M.; Cipriani, Andrea; Furukawa, Toshi A.; Salanti, Georgia; Leucht, Stefan (Lancet, 2022)
Background: Schizophrenia is a common, severe, and usually chronic disorder. Maintenance treatment with antipsychotic drugs can prevent relapse but also causes side-effects. We aimed to compare the efficacy and tolerability of antipsychotics as maintenance treatment for non-treatment resistant patients with schizophrenia. Methods: In this systematic review and network meta-analysis, we searched, without language restrictions, the Cochrane Schizophrenia Group's specialised register between database inception and April 27, 2020, PubMed from April 1, 2020, to Jan 15, 2021, and the lists of included studies from related systematic reviews. We included randomised controlled trials (RCTs; ≥12 weeks of follow-up) that recruited adult participants with schizophrenia or schizoaffective disorder with stable symptoms who were treated with antipsychotics (monotherapy; oral or long-acting injectable) or placebo. We excluded RCTs of participants with specific comorbidities or treatment resistance. In duplicate, two authors independently selected eligible RCTs and extracted aggregate data. The primary outcome was the number of participants who relapsed and was analysed by random-effects, Bayesian network meta-analyses. The study was registered on PROSPERO, CRD42016049022. Findings: We identified 4157 references through our search, from which 501 references on 127 RCTs of 32 antipsychotics (comprising 18 152 participants) were included. 100 studies including 16 812 participants and 30 antipsychotics contributed to our network meta-analysis of the primary outcome. All antipsychotics had risk ratios (RRs) less than 1·00 when compared with placebo for relapse prevention and almost all had 95% credible intervals (CrIs) excluding no effect. RRs ranged from 0·20 (95% CrI 0·05–0·41) for paliperidone oral to 0·65 (0·16–1·14) for cariprazine oral (moderate-to-low confidence in estimates). Generally, we interpret that there was no clear evidence for the superiority of specific antipsychotics in terms of relapse prevention because most comparisons between antipsychotics included a probability of no difference. Interpretation: As we found no clear differences between antipsychotics for relapse prevention, we conclude that the choice of antipsychotic for maintenance treatment should be guided mainly by their tolerability. Funding: The German Ministry of Education and Research and Oxford Health Biomedical Research Centre.
CRIS-Team Scopus Importer:2022-03-04